Muscle damage slows oxygen uptake kinetics during moderate-intensity exercise performed at high pedal rate - Molina, Renato [UNESP]; Denadai, Benedito Sergio [UNESP] (Canadian Science Publishing, Nrc Research Press, 2011)
This study aimed to investigate the dependence of oxygen uptake (VO2) kinetics on pedal cadence during moderate-intensity exercise following exercise-induced muscle damage (EIMD). Twenty untrained males were randomly assigned to a 50 revolution per minute (rpm) (age, 23.3 +/- 1.8 years; VO2max, 38.9 +/- 2.8 mL . kg(-1) . min(-1)) or 100 rpm group (age, 24.4 +/- 3.5 years, VO2max, 42.9 +/- 4.3 mL . kg(-1) . min(-1)). Participants completed "step" tests to moderate-intensity exercise from an unloaded baseline on a cycle ergometer before (baseline) and at 24 and 48 h after muscle-damaging exercise (10 sets of 10 eccentric contractions performed on an isokinetic dynamometer with a 2-min rest between each set). Pedal cadence was kept constant throughout each cycling trial (50 or 100 rpm). There were no changes in phase II pulmonary VO2 kinetics following EIMD for the 50 rpm group (baseline = 35 +/- 4 s; 24 h = 35 +/- 7 s; and 48 h = 36 +/- 9 s). However, the phase II VO2 was significantly greater at 24 h (59 +/- 27 s) compared with baseline (39 +/- 6 s) and 48 h (40 +/- 9 s) for the 100 rpm group. It is concluded that the effects of EIMD on phase II VO2 kinetics during moderate-intensity cycling exercise is dependent on pedal cadence. The slower VO2 kinetics after muscle damage suggests that type II fibers are involved during transition to moderate-intensity exercise at high pedal cadence.
Keywords: eccentric; creatine kinase; cycling; isokinetic; lactate threshold; moderate intensity